Four or More Cesarean Sections, is it Still Safe? - Yücel, Burak; Kadiroğulları, Pınar; Karahasan, Onur; Aydın, Turgut; Seçkin, Kerem Doğa; Gedikbaşı, Ali (Gynecology Obstetrics & Reproductive Medicine, 2017)
Objective: We aimed to compare the maternal and neonatal complications in women who had undergone fourth or more cesarean section with to women who had undergone second or third cesarean section. Study Design: 162 women who had four or more cesarean section (study group) and 228 women who had undergone second or third cesarean section (control group) were reviewed retrospectively. Demographic features, obstetric, intraoperative, postpartum and neonatal complications were determined in both groups. Results: The preoperative hematocrit values were lower in study group (35.63.6) than the control group (36.64.3), (p <0.001). Patients with four or more cesarean section had an increased rate (24.7%) of intra-abdominal dense adhesions compared with the controls (14.9%), (p<0.001). Blood transfusion rate was higher in the study group (8.6% to 3.5%, p=0.043). Except these; frequencies of obstetric, intraoperative, postpartum and neonatal complications were similar between groups. Conclusion: We found that multiple CSs (four or more) do not increase the risk of maternal or neonatal complications except the rate of maternal anemia, dense adhesions and need for blood transfusion according to the results of our study. Fourth or more cesarean section appears to be still a safe procedure.